PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP SEMANGAT KERJA PADA VILYA COMPUTER KARANGASEM - Sujana, I Made; Suandi, I Nyoman; Astra, I Gede Rentawan Wana (Jurnal MBE Manajemen Bisnis, Equilibrium, 2023)
Leaders must also be able to provide encouragement and motivate employees to work well in order to achieve goals desired by the company. Leadership and motivation have an immediate effect on employee morale. Referring to the fact that researchers interested in conducting research on "The Influence of Leadership and Motivation Against Morale On Vilya Computer Karangasem". This study aims to determine the influence of leadership and motivation on morale at Vilya Computer Karangasem simultaneously and partially. This research was conducted at Vilya Computer Karangasem which is located at Jl. Untung Surapati No.68 X Amlapura-Bali with a total sample of 25 respondents. Variables consist of Leadership, Motivation and Morale. Data source used is primary data and secondary data. The conclusion of this research is that leadership and motivation have positive and significant influence simultantly or partially to work spirit at Vilya Computer Karangasem.